The Effect of Inhalation Aromatherapy With Damask Rose (Rosa Damascena) on the Pain of Elderly After Knee Arthroplasty - Farideh Bastani; Parvaneh Samady Kia; Hamid Haghani (Iran University of Medical Sciences, 2017)
Background: Acute postoperative pain is anticipated as a common problem in orthopedic surgeries especially arthroplasty which can cause harmful effects to the body and the psyche of the person. Currently, non-pharmacological approaches such as aromatherapy are taken into account pain relief along with pharmaceutical methods. The aim of the current study was to determine the effect of the aromatherapy with the Damask Rose on pain of elderly patients after knee arthroplasty surgery. Methods: This study is a non-randomized clinical trial, 80 elderly patients underwent knee arthroplasty surgery were selected from two hospitals (Moheb and Shafa) according to inclusion criteria and enrolled into the study by simple random sampling. Patients were divided into control and experimental groups. Interventions with Damask Rose were perfomred 24 hours after surgery and there were 4 sessions within 2 hours with 30 minutes interval.  Visual Analog Scale (VAS) was used to measure pain and daya was analyzed using SPSS version 16. Results: In the experimental group, the pain intensity was significantly different before and after the intervention (P < 0.001). However, there was no significant difference in the pain intensity of the control group before and after the intervention (P = 0.66). Comparing the difference in pain scores before and after the intervention, there was a significant decrease in this score after the intervention in the experimental group compared to the control group and before intervention (P < 0.001). Conclusion: The study demonstrate that aromatherapy has a positive effect on reducing the postoperative pain of the elderly, and it can be used as a complementary medicine which is cost effective, safe, and easy to perform.